Effectiveness of Painting Based Game on Self-esteem and Quality of Life in Children with Hearing Impairment - Sima Ali Hosseini; Fateme Mohammadi; Salman Khazaei; Tayebeh Hassan Tehrani; Marzieh Effatpanah (پژوهان)
Background and Objectives: Children with hearing impairments often face challenges in developing self-esteem and maintaining quality of life due to communication barriers and interactive limitations. Group play activities, by providing opportunities for interaction and collaboration, can serve as an effective tool to address these challenges. Therefore, the present study aimed to determine the impact of painting based game on self-esteem and quality of life of children with hearing impairments. Materials and Methods: The present study was a randomized controlled trial, and a total of 62 deaf children from a welfare center affiliated with the Hamadan University of Medical Sciences, Iran, were selected. They were then randomly assigned to either the play therapy group or the control group. The experimental group participated in group play sessions for 90 minutes every week over six sessions. In addition, the Coopersmith Self-Esteem Inventory and the Quality of Life Children's questionnaire were completed as self-reports. Results: The results indicated a statistically significant increase in the average scores of self-esteem and quality of life and their dimensions in the experimental group compared to the control group immediately and one month after the intervention (P<0.05). Conclusion: Painting-based games can have positive and lasting effects on the self-esteem and quality of life of children with hearing impairments. It seems necessary to create the conditions for conducting group painting based game in centers specialized for children with hearing impairments.